DESIGN OF GROUND WATER QUALITY AND CAPACITY MONITORING SYSTEM FOR ASR INFILTRATION WELL USING WIRELESS - Alam, Hilman Syaeful; Munandar, Aris; Soetraprawata, Demi; Turnip, Arjon (Teknologi Indonesia, 2013)
Design of a monitoring system for the quality and capacity of water absorption wells type Aquifer Storage and Recovery (ASR) using wireless system has been conducted by monitoring changes in well water surface level, the rate of change of fl ow capacity (fl ow rate) and changes in water quality (turbidity). In order to determine the performance of the system, we conducted several tests by placing a sensor and a receiver by two different distances, i.e. the distance of 1 m (short distance) and the actual condition of 35 m (long distance). The results of the system design consist of a wireless monitoring system hardware and data acquisition system software able to display online and in real time. Based on the test results, the value of the total error due to repeatability and linearity for flow rate sensors, water level and turbidity using short-distance wireless systems, are respectively 2.77%, 1.77% and 3.65%. As for the wireless remote system, they are respectively 1.43%, 1.83% and 2.43%. So, the monitoring system of groundwater quality and capacity for infi ltration well using the wireless system can be applied to the actual distance of 35 m, because the error rate due to the infl uence of the distance between the transmitter and the receiver is relatively small, and even better when compared with the short distance ( 1 m).